1989
DOI: 10.1136/bmj.299.6706.1010
|View full text |Cite
|
Sign up to set email alerts
|

Dipstick haematuria and bladder cancer in men over 60: results of a community study.

Abstract: Denied by relativc 5 Not requcstcd 3 1 (Chisholm GD. Time to end the softly softly approach on harvesting organs for transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
0
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 16 publications
3
56
0
2
Order By: Relevance
“…In the present study, we report our early experience concerning the development of UC in a risk group of workers, employed in a Ligurian coke plant, who were exposed to the products formed during coke production for a mean period of 16 years. In accordance with other authors, our screening protocol also included an extensive history and physical examination, in order to identify possible associated risk factors or suspect lesions for UC, followed by non-invasive urinary tests which could help to distinguish healthy individuals from those who required further examination such as cystoscopy, urography or CT scan [9][10][11][16][17] . Particularly, we decided to combine the execution of urine analysis with urinary cytology and the uCyt+ assay in order to produce a high detection rate for all forms of UC, limiting the need for cystoscopy only in the event of a positive urine analysis [18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we report our early experience concerning the development of UC in a risk group of workers, employed in a Ligurian coke plant, who were exposed to the products formed during coke production for a mean period of 16 years. In accordance with other authors, our screening protocol also included an extensive history and physical examination, in order to identify possible associated risk factors or suspect lesions for UC, followed by non-invasive urinary tests which could help to distinguish healthy individuals from those who required further examination such as cystoscopy, urography or CT scan [9][10][11][16][17] . Particularly, we decided to combine the execution of urine analysis with urinary cytology and the uCyt+ assay in order to produce a high detection rate for all forms of UC, limiting the need for cystoscopy only in the event of a positive urine analysis [18][19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of urothelial cancer in patients with microscopic hematuria is markedly lower than that in patients with macroscopic hematuria and is usually no more than several percent. 4,5 However, because the number of patients with microscopic hematuria has been increasing with the spread of health examinations, the development of a screening method for patients with microscopic hematuria who need closer urologic examination, such as cystoscopy, is required. 12 Urologists commonly use urine cytology, ultrasonography and intravenous urography as screening tests before cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Most laboratories consider a negative result as normal, based on findings in referred patients and on population studies showing that urinary tract tumors and other serious diseases are found in those with even trace amounts of blood on test strips (2)(3)(4). In two population studies, dipsticks were positive for blood in 3% of men of all ages (3 ) and in 13% of those over 60 years (4 ).…”
mentioning
confidence: 99%
“…Recent recommendations support a repeat urinalysis after 48 h to confirm positive dipstick findings and a work-up that includes confirmation of the dipstick results by microscopic urinalysis (14,15 ) and identification of dysmorphic RBCs (14,15 ). This approach decreases the sensitivity for detecting serious urothelial diseases because of the intermittent nature of hematuria in patients with serious urothelial disease (2)(3)(4)16 ), the known problems with the precision and accuracy of microscopic urinalysis (2,17,18 ), with intralaboratory CV of 25-50% (8,19 ), and with the possibility of concomitant dysmorphic RBCs in the urine in the presence of urothelial cancer (20 ). It has been pointed out that current data are inadequate to support clear-cut recommendations regarding the management of microscopic hematuria (15 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation